Omnichannel Strategy: Its Impact on Customer Satisfaction and Retention - Ilyas, Andre; Dianti, Muthia Rahma; Mirsal (Jurnal Informatika Ekonomi Bisnis, 2025)
This paper explores the impact of omnichannel strategies on customer satisfaction and retention. The scope of the research includes industries such as retail, technology, and financial services, focusing on how integrated communication channels, including physical stores, online platforms, and mobile applications, enhance customer experiences. The objectives are to analyze the relationship between omnichannel strategies and customer loyalty, and to investigate the effectiveness of these strategies in improving retention rates. A mixed methods approach was employed, combining quantitative surveys and qualitative interviews. Data was gathered from over 500 respondents across various industries, and results were analyzed using statistical and thematic methods. The findings show that service consistency, personalization, and convenience are critical factors driving customer satisfaction and retention. Businesses that integrate these factors across all touchpoints report higher levels of customer loyalty and long term retention. The study concludes that omnichannel strategies are essential for businesses seeking to enhance customer experiences and improve customer retention. These findings have practical implications for companies looking to optimize their customer engagement strategies in today’s competitive market.